ANALYSIS OF IMPROVING GOOD UNIVERSITY GOVERNANCE: A CASE STUDY OF THE IMPLEMENTATION OF INDEPENDENT LEARNING ON AN INDEPENDENT CAMPUS (MBKM) - Hilmi; Dy Ilham; Arnawan Hasibuan; Widyana Verawaty Siregar (Universitas Efarina, 2024)
According to the Organization for Economic Co-operation and Development stated the challenges facing universities today were the creation of knowledge through research, transfer of knowledge through education, development of human resources and development of culture and society, including creating innovations according to developing conditions. As a country that has a low percentage of the population attending school at the higher education level, Indonesia was at the level of 31.5%, the remaining 68.5% of Indonesian children aged 19-23 years have not yet had the chance to go to college. The challenges faced by Indonesia was developing a 4.0 curriculum known as Merdeka belajar campus merdeka (Independent Learning Independent Campus (MBKM). This study used a quantitative type with a simple random sampling technique and then distributed questionnaires to respondents from the MBKM observation unit in all state campuses in Aceh. The results showed that the variables of leadership style and intellectual capital had a positive effect on good university governance, meaning that the more transformative a person's leadership style and the higher the quality of organizational resources at the university can improve good governance university. The purpose of this research was to make state universities more aware in improving good governance university.